Serum Endocrine Profile in Relation to Estrus Synchronization in Surti Does - CT, Chaudhri; Patel, SB; Chaudhari, SS; Atara, VB; Patel, DK (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The serum progesterone and estradiol profiles during synchronization of estrus by buck effect and PGF2α treatments were monitored in Surti does. Total eighteen non-pregnant does selected were evenly divided into 3 groups, 6 does in each group. The does of Group I were teased with a sexually active-apronized buck; and those of Group II were treated with PGF2α, i.e., Inj. Lutalyse® @ 7.5 mg/doe IM twice 11 days apart, while the Group III served as untreated control. Blood samples were collected from all the animals on day 0 (before 1st PGF2α injection), 3rd day (during treatment), 11th day (before 2nd PGF2α injection), 14th day (after treatment) and 40th day (post-service) by jugular vein puncture. The serum separated was stored at -20°C till further analysis. In all the three groups, 83.33% does, conceived at first service in the sampling cycle. The overall mean serum progesterone concentration of Group I does (5.82±0.72 ng/ml) was significantly higher (p<0.01) as compared to Group II (2.93±0.38 ng/ml) and III (2.88±0.30 ng/ml). Similarly, the overall mean serum progesterone concentration of Surti does on day 0 (2.65±0.46 ng/ml), 3rd (2.56±0.80 ng/ml), 11th (4.45±0.84 ng/ml) and 14th (3.40±0.63 ng/ml) did not differ significantly, but the overall mean level at day 40 (6.31±0.45 ng/ml) was significantly (p<0.01) higher, because most of animals became pregnant at that time. The overall mean serum oestradiol-17β levels of Group I (24.40±2.98 pg/ ml) was significantly higher (p<0.01) than in Group II (15.77±1.77 pg/ml) and III (12.21±1.45 pg/ ml). On the other hand, the overall mean serum oestradiol-17β levels of Surti does on day 0 (12.89±1.21 pg/ml), 3rd (15.84±1.74 pg/ml), 11th (14.81±1.96 pg/ml), 14th (22.15±2.97 pg/ml) and 40th (21.64±5.16 pg/ml) did not differ significantly (p>0.05) and the slightly higher overall mean level found at 40th day might be the influence of the non-pregnant does at first service in the cumulative animals. The hormonal profile reflected the initiation of cyclicity and establishment of pregnancy in treated and control animals.